A coated vulcanizing agent, asphalt stabilizer and preparation method and application thereof
Through the coating vulcanizing agent technology, the micro-crosslinked shell material and parent material are used to coat sulfur to form a microcapsule structure, which solves the problem of poor stability of modified asphalt during storage and transportation, and achieves high stability of modified asphalt Improved performance and comprehensive performance.
Patent Information
- Application Number
- CN202310168793.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-02-27
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2043-02-27
AI Technical Summary
The existing modified asphalt materials have poor stability during storage and transportation, which is prone to segregation and stratification, and the performance indicators will irreversibly attenuate during thermal storage, making it difficult to meet the high and low temperature performance requirements.
The coated vulcanizing agent is used to coat sulfur through micro-crosslinked shell material and parent material to form a microcapsule structure. The sulfur is in a crystal state at room temperature and is slowly released when the temperature rises, avoiding excessive cross-linking and promoting asphalt and polymerization. Full cross-linking of objects.
It effectively improves the compatibility and comprehensive performance of modified asphalt, improves its storage stability, prevents separation, delays performance attenuation, and meets the high and low temperature performance requirements.
Smart Images

Figure CN116178796B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of asphalt modification, and in particular to a coated vulcanizing agent, an asphalt stabilizer, and a preparation method and application thereof. Background Art
[0002] With the development of highway transportation, especially the rapid development of high-grade highways, the number of asphalt pavements has been increasing and the grade has been improving. Ordinary asphalt pavement refers to various types of pavement paved with road asphalt materials mixed into mineral materials. Asphalt materials improve the ability of paving aggregates to resist damage to the road surface caused by driving and natural factors, making the road surface smooth, dust-free, impermeable and durable. Compared with cement concrete pavement, asphalt pavement has the advantages of smooth surface, no joints, comfortable driving, wear resistance, low vibration, low noise, short construction period, and simple maintenance and repair. It is the most widely used high-grade pavement in road construction.
[0003] With the increase in traffic volume and the large-scale vehicles, the quality requirements for asphalt pavements are getting higher and higher. As a new pavement material, modified asphalt avoids the problem that ordinary asphalt mixtures are prone to brittle cracking, resulting in cracks in the pavement and poor high temperature resistance. It can make asphalt comprehensively improved in terms of temperature sensitivity, stability, durability, adhesion, and aging resistance, and can improve the comprehensive performance of the pavement. This type of material can meet the requirements of high and low temperature performance at the same time, and has the advantages of wide applicability, and has become the main force in modified asphalt products. At present, the common modified asphalt is modified by SBS or rubber, which can effectively improve the high temperature resistance, rutting resistance, fatigue resistance and elastic recovery ability of asphalt materials. However, due to the large physical differences between asphalt and modifiers, it is not easy to form a stable modified asphalt system, which will cause the modifier and the base asphalt to separate and stratify, resulting in uneven modified asphalt in the upper and lower parts. Secondly, irreversible performance index attenuation will occur during hot storage. This type of material has the problem of poor storage and transportation stability. Adding stabilizers to this type of material is an effective way to solve this problem. Modified asphalt stabilizer is a raw material necessary for the production of modified asphalt. The addition of stabilizer can promote the formation of the three-dimensional network structure of the modifier, improve the compatibility of the modifier and the matrix asphalt, reduce the segregation softening point difference, avoid the attenuation of thermal storage indicators, and make the modified asphalt system stable.
[0004] Sulfur is currently the most excellent cross-linking agent. The common modified asphalt stabilizer in the prior art improves storage stability by adding sulfur. The vulcanized rubber prepared with sulfur as a cross-linking agent has good elasticity and anti-flexing properties. Because of this, sulfur is widely used in the processing of rubber products with its excellent performance. During use, due to the difference in the solubility of sulfur in rubber at different temperatures, when the amount of vulcanizer is large, part of the sulfur will migrate to the surface of the rubber during the storage of the rubber, causing the adhesiveness of the rubber to decrease and affecting the appearance of the product, that is, the common frosting problem in the industry. The frosting problem not only reduces the performance of the rubber and the product, but also causes waste of resources and environmental pollution, which needs to be urgently solved. However, the amount and speed of sulfur addition have a great influence on the reaction results. If sulfur is added too quickly or too much at one time, the asphalt-polymer will be partially or completely over-cross-linked and condensed into a colloid, causing flow difficulties and inability to continue production. Liquid stabilizers that can reduce interfacial energy by adding high-aromatic heavy oil or using water-based methods have also appeared on the market. Although these stabilizers can achieve the purpose of improving storage stability, they cannot improve or delay the performance degradation of modified asphalt during hot storage. Although sulfur-containing stabilizers prepared by adding some powdered additives have improved the local or overall cross-linking phenomenon of the stabilizer to a certain extent, they cannot achieve some special performance requirements of modified asphalt by increasing the stabilizer dosage. Therefore, how to improve the compatibility and comprehensive performance of modified asphalt, improve its storage stability, prevent the segregation of modified asphalt, and delay its performance degradation is an urgent task, and it is also a hot spot and frontier in the study of modified asphalt.
[0005] In order to improve the utilization rate of the vulcanizing agent, the existing method of coating sulfur is adopted. Microcapsule sulfur is coated with silica, PMMA, PS, GO, etc. The hardness and tensile stress of sulfur vulcanizates coated with these single materials are basically unchanged. Because the coating material is a monophilic material, although after coating, the dispersibility of the vulcanizing agent in the rubber is improved, the utilization efficiency of sulfur is improved, but the release speed is fast and the role of the outer coating material (shell material residue) is only to improve the dispersibility. It is still difficult to meet the comprehensive performance improvement of modified asphalt and effectively avoid the segregation of modified asphalt and delay the problem of performance degradation. Summary of the invention
[0006] The present invention provides a coated vulcanizing agent, an asphalt stabilizer, and a preparation method and application thereof. The coated vulcanizing agent adopts a micro-crosslinked shell material and uses an amphiphilic material. The shell material residue is equivalent to a filler interspersed in a rubber matrix. The small particle size effect and the amphiphilic effect have a certain reinforcing effect and stabilizing effect on the rubber, and play a role as a physical crosslinking point in the vulcanized rubber; sulfur can be slowly released, which not only effectively prevents excessive crosslinking of asphalt and polymer, but also promotes a more complete crosslinking reaction of asphalt and polymer, thereby improving the performance of asphalt, improving its storage stability, preventing segregation, and delaying its performance degradation, thereby solving the problems existing in the prior art.
[0007] One of the technical solutions adopted by the present invention is:
[0008] A coated vulcanizing agent is prepared by a preparation method comprising the following steps:
[0009] (1) S was dissolved in CS2, and then added to isopropanol, and a surfactant was added. The mixture was stirred magnetically for 30 min, and toluene was added dropwise. After stirring for 30 min, the amphiphilic block copolymer was added, and stirring was continued to prepare solution 1;
[0010] (2) adding a compound containing an isocyanate functional group into an organic solvent to prepare a solution 2;
[0011] (3) Add the prepared "Solution 2" to "Solution 1", stir and react for 24 hours, then remove the solvent to obtain a coated vulcanizing agent.
[0012] Furthermore, in step (1), the mass ratio of CS2:S is 10:3-4, the volume ratio of CS2 solution to isopropanol is 1:1-3, and the volume ratio of isopropanol to toluene is 10:0.5-3;
[0013] The surfactant is one or more of fatty acid glyceride, fatty acid sorbitan, polysorbate, sodium dodecyl sulfate, and sodium dodecyl sulfonate; the amphiphilic block copolymer is polystyrene-polyoxyethyleneimine (PS-b-PEI) and / or polystyrene-polyacrylamide (PS-b-PAM).
[0014] Further, the compound containing an isocyanate functional group in step (2) includes one or more of isophorone diisocyanate, toluene diisocyanate, diphenylmethane diisocyanate, hexamethylene diisocyanate, methylene di(4-cyclohexyl isocyanate), and tetramethylxylyl diisocyanate;
[0015] The organic solvent is diphenyl ether and / or toluene.
[0016] Furthermore, the reaction temperature in step (3) is 10 to 60°C.
[0017] Further, the reaction process in step (3) is as follows:
[0018]
[0019] The second technical solution adopted by the present invention is:
[0020] An asphalt stabilizer prepared using the coated vulcanizing agent as described above comprises the following components in parts by weight:
[0021]
[0022] Furthermore, the accelerator comprises one or more of thiurams, thiazoles, dithiocarbamates, and aldehyde amines;
[0023] The auxiliary promoter comprises one or more of zinc oxide, magnesium oxide, magnesium carbonate, calcium oxide and calcium carbonate;
[0024] The activated carbon has a mesh size of 100 to 400, preferably 200 to 400.
[0025] The third technical solution adopted by the present invention is:
[0026] A method for preparing the asphalt stabilizer as described above, characterized in that it comprises the following steps:
[0027] The coated vulcanizing agent and activated carbon are mixed with each other at 50°C in a high-speed mixer for 20 to 30 minutes, and after adding the accelerator and the co-accelerator, the mixture is further mixed with each other at 50°C in a high-speed mixer for 30 minutes to obtain the product.
[0028] The fourth technical solution adopted by the present invention is:
[0029] Provided is the use of the above-mentioned asphalt stabilizer in the preparation of anti-segregation modified asphalt material.
[0030] Furthermore, the asphalt stabilizer is added in an amount of 0.3%-0.4% of the total weight of the modified asphalt.
[0031] Beneficial effects of the present invention:
[0032] The coated vulcanizing agent of the present invention adopts a micro-crosslinked shell material and uses an amphiphilic material. When used, the shell material residue is equivalent to a filler interspersed in the rubber matrix. The small particle size effect and the amphiphilic effect have a certain reinforcing effect and stabilizing effect on the rubber, and play the role of a physical crosslinking point in the vulcanized rubber.
[0033] The microcapsules specifically selected in the present invention are PS-b-PEI and / or PS-b-PAM. The surface layer of the microcapsules is cross-linked by isocyanate groups to encapsulate sulfur in the microcapsules. The sulfur is in a crystalline state at room temperature and pressure. When the temperature is raised above its melting temperature, the shell layer softens or breaks and degrades to slowly release the sulfur, or the molten sulfur flows out through the porous structure of the shell material. The slow release of sulfur not only effectively prevents excessive cross-linking of asphalt and polymer, but also promotes a more complete cross-linking reaction between asphalt and polymer, thereby improving the performance of asphalt. At the same time, the microcapsules play a reinforcing role in asphalt. Due to the presence of the PS segment of the microcapsule, it has good affinity with PS in SBS, and the presence of PEI / PAM micro-crosslinking also has good compatibility with asphalt. The presence of the crosslinking can serve as a three-dimensional node to improve stability. The preparation method of the coated vulcanizing agent is simple and easy, the raw material source is wide, the price is low, the reaction conditions are mild, and it is suitable for large-scale production; the modified asphalt stabilizer prepared by the method can effectively improve the compatibility and comprehensive performance of the modified asphalt, improve its storage stability, prevent the segregation of the modified asphalt, and delay its performance degradation. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 It is a schematic diagram of the coated vulcanizing agent microcapsule of the present invention;
[0035] Figure 2 It is a schematic diagram of forming a cross-linked layer on the surface of the coated vulcanizing agent microcapsule of the present invention. DETAILED DESCRIPTION
[0036] In order to clearly illustrate the technical features of this solution, the present invention is described in detail below through specific implementation methods.
[0037] The experimental methods, detection methods, etc. involved in the following embodiments, unless otherwise specified, are all conventional experimental methods, detection methods, etc. available in the prior art.
[0038] Example 1
[0039] A preparation method of an asphalt stabilizer comprises the following steps:
[0040] (1) 3 g S was dissolved in 10 g CS2, and then added to 20 ml isopropanol, and 0.5 g of surfactant fatty acid sorbitan was added, and magnetic stirring was performed for 30 min. Then, 2 ml of toluene was added dropwise, and after stirring for 30 min, 2 g of amphiphilic block copolymer PS-b-PEI was added, and stirring was continued to prepare solution 1;
[0041] (2) adding 0.3 g of MDI, a compound containing an isocyanate functional group, into 1 ml of toluene as an organic solvent to prepare solution 2;
[0042] (3) Add the prepared "Solution 2" to "Solution 1", stir and react for 24 hours, then remove the solvent to obtain a coated vulcanizing agent;
[0043] (4) 100 parts of the coated vulcanizing agent and 5 parts of activated carbon were blended in a high-speed mixer at 50° C. for 20 minutes, 30 parts of thiuram disulfide and 30 parts of calcium carbonate were added, and the mixture was blended in a high-speed mixer at 50° C. for 30 minutes to obtain an asphalt stabilizer.
[0044] Example 2
[0045] A preparation method of an asphalt stabilizer comprises the following steps:
[0046] (1) 3 g S was dissolved in 10 g CS2, and then added to 20 ml isopropanol, and 0.5 g of surfactant fatty acid sorbitan was added, and magnetic stirring was performed for 30 min. Then 2 ml of toluene was added dropwise, and after stirring for 30 min, 2 g of amphiphilic block copolymer PS-b-PAM was added, and stirring was continued to prepare solution 1;
[0047] (2) adding 0.3 g of MDI, a compound containing an isocyanate functional group, into 1 ml of toluene as an organic solvent to prepare solution 2;
[0048] (3) Add the prepared "Solution 2" to the "Solution 1", stir and react for 24 hours, then remove the solvent to obtain a coated vulcanizing agent.
[0049] (4) 100 parts of the coated vulcanizing agent and 5 parts of activated carbon were blended in a high-speed mixer at 50° C. for 20 minutes, and 40 parts of ammonium dithiocarbamate and 30 parts of zinc oxide were added and blended in a high-speed mixer at 50° C. for 30 minutes to obtain an asphalt stabilizer.
[0050] Example 3
[0051] A preparation method of an asphalt stabilizer comprises the following steps:
[0052] (1) 3 g S was dissolved in 10 g CS2, and then added to 15 ml isopropanol, and 0.5 g of surfactant polysorbate was added, and magnetic stirring was performed for 30 min. Then 2 ml of toluene was added dropwise, and after stirring for 30 min, 2 g of amphiphilic block copolymer PS-b-PEI was added, and stirring was continued to prepare solution 1;
[0053] (2) adding 0.5 g of the isocyanate functional compound TDI to 1 ml of the organic solvent toluene to prepare solution 2;
[0054] (3) Add the prepared "Solution 2" to the "Solution 1", stir and react for 24 hours, then remove the solvent to obtain a coated vulcanizing agent.
[0055] (4) 100 parts of the coated vulcanizing agent and 5 parts of activated carbon were blended in a high-speed mixer at 50° C. for 20 minutes, 30 parts of thiuram disulfide and 40 parts of calcium carbonate were added, and the mixture was blended in a high-speed mixer at 50° C. for 30 minutes to obtain an asphalt stabilizer.
[0056] Example 4
[0057] A preparation method of an asphalt stabilizer comprises the following steps:
[0058] (1) 3 g S was dissolved in 10 g CS2, and then added to 20 ml isopropanol, and 0.5 g of surfactant fatty acid glyceride was added, and magnetic stirring was performed for 30 min. Then 1 ml of toluene was added dropwise, and after stirring for 30 min, 2 g of amphiphilic block copolymer PS-b-PEI was added, and stirring was continued to prepare solution 1;
[0059] (2) adding 0.3 g of MDI, a compound containing an isocyanate functional group, into 1 ml of toluene as an organic solvent to prepare solution 2;
[0060] (3) Add the prepared "Solution 2" to the "Solution 1", stir and react for 24 hours, then remove the solvent to obtain a coated vulcanizing agent.
[0061] (4) 100 parts of the coated vulcanizer and 5 parts of activated carbon were blended in a high-speed mixer at 50° C. for 20 minutes, 40 parts of dibenzothiazole disulfide and 40 parts of calcium carbonate were added, and the mixture was blended in a high-speed mixer at 50° C. for 30 minutes to obtain an asphalt stabilizer.
[0062] Example 5
[0063] A preparation method of an asphalt stabilizer comprises the following steps:
[0064] (1) 3.5 g S was dissolved in 10 g CS2, and then added to 20 ml isopropanol, and 0.5 g of surfactant fatty acid sorbitan was added, and magnetic stirring was performed for 30 min. Then, 2 ml of toluene was added dropwise, and after stirring for 30 min, 2 g of amphiphilic block copolymer PS-b-PAM was added, and stirring was continued to prepare solution 1;
[0065] (2) adding 0.5 g of MDI, a compound containing an isocyanate functional group, into an organic solvent, toluene, to prepare a solution 2;
[0066] (3) Add the prepared "Solution 2" to the "Solution 1", stir and react for 24 hours, then remove the solvent to obtain a coated vulcanizing agent.
[0067] (4) 100 parts of the coated vulcanizer and 10 parts of activated carbon were blended in a high-speed mixer at 50° C. for 20 minutes, and 40 parts of dibenzothiazole disulfide and 30 parts of calcium carbonate were added and blended in a high-speed mixer at 50° C. for 30 minutes to obtain an asphalt stabilizer.
[0068] 1. Modified asphalt storage stability segregation test
[0069] 1. Preparation of SBS modified asphalt
[0070] The raw asphalt and SBS modifier were mixed in a certain proportion at 180±5°C, ground at a speed of 4000-5000rpm until uniform, stabilizer was added, and stirred and grown at 175±5°C for 4h to obtain modified asphalt.
[0071] The amount of stabilizer added in Examples 1 to 5 of the present invention is 0.31% of the total weight of the modified asphalt, and the amount of sulfur added in the comparative example is 0.15% of the total weight of the modified asphalt. The stabilizer is added in a one-time manner.
[0072] The storage stability segregation test was performed according to JTG E20-2011 standard.
[0073] The results are shown in Table 1 below:
[0074] Table 1
[0075]
[0076] The modified asphalt to which the asphalt stabilizer of Examples 1 to 5 of the present invention is added has excellent storage stability. After the stabilizer is added once, the stabilizer does not show partial or overall excessive cross-linking, and the stabilizer is gradually and evenly dispersed. As the stirring and development time increases, the surface of the modified asphalt is smooth without obvious granularity, and the storage stability segregation can meet the performance requirements.
[0077] By comparing the effects, after the one-time addition of sulfur, even with a smaller amount added than in the present application, it still causes partial excessive cross-linking between the asphalt and the modifier, and the modified asphalt presents a "jelly-like" gel state. The sulfur cannot be evenly dispersed. With stirring, the modified asphalt presents a gel state as a whole. The development time is prolonged without obvious relief, and the storage stability segregation cannot meet the performance requirements. In terms of the preparation of SBS modified asphalt, the commercially available sulfur-containing stabilizer and the embodiments of the present invention can make the storage stability segregation meet the performance requirements at the same dosage.
[0078] 2. Special modified asphalt test
[0079] The preparation of special modified asphalt follows the following steps: mix the raw asphalt and high viscosity agent in a certain proportion at 185±5°C, grind to a uniform state at a speed of 4000-5000rpm, add a stabilizer, stir and develop at 180±5°C for 6h to obtain special modified asphalt.
[0080] The stabilizer of Example 1 of the present invention and a commercially available stabilizer were selected, and the added amounts were 0.31% and 0.39% of the total weight of the special modified asphalt respectively. The added amount of sulfur element in the comparative example was 0.19% of the total weight of the special modified asphalt, and the stabilizer was added in a one-time manner; the added amount of the above-mentioned high viscosity agent was 9.0% of the total weight of the special modified asphalt.
[0081] The softening point, segregation and 60°C dynamic viscosity tests were performed according to JTG E20-2011 standard.
[0082] The results are shown in Table 2 below:
[0083] Table 2
[0084]
[0085] Taking the stabilizer of Example 1 as an example, compared with commercially available sulfur-containing stabilizers and sulfur alone, it can be seen that when the sulfur alone is added in a smaller amount, it promotes local excessive cross-linking of asphalt and modifier, and the special modified asphalt also presents a "jelly-like" gel state and cannot be evenly dispersed. Comparing the present application with the commercially available stabilizer, when the stabilizer addition amount is low, the present application can prepare high-viscosity modified asphalt with excellent storage stability, while the storage stability of the modified asphalt prepared by the commercial stabilizer cannot meet the performance requirements, and the viscosity is low. Increasing the stabilizer dosage, the present application can prepare a higher grade of high-viscosity modified asphalt, while the commercial stabilizer causes the asphalt to present a gel state due to the increase in the stabilizer addition, and cannot be evenly dispersed. Compared with commercially available stabilizers, the stabilizer of the present invention has a higher dosage and a high utilization rate. It is used to prepare high-viscosity modified asphalt and high softening point modified asphalt, which can meet the special needs of asphalt. In addition, the stabilizer of the present invention is cost-effective and controllable.
[0086] The asphalt stabilizer in the embodiment of the present invention is fully and effectively utilized based on a significantly higher addition amount.
[0087] The above specific implementation manner cannot be used as a limitation on the protection scope of the present invention. For those skilled in the art, any substitution, improvement or change made to the implementation manner of the present invention falls within the protection scope of the present invention.
[0088] The matters not described in detail in the present invention are all known technologies to those skilled in the art.
Claims
1. A coated vulcanizing agent, characterized in that: It is prepared by a preparation method comprising the following steps: (1) S is dissolved in CS2, and then added to isopropanol together with a surfactant, and magnetically stirred for a certain period of time, toluene is added dropwise therein, and after stirring, the amphiphilic block copolymer is added, and stirring is continued to prepare solution 1; (2) adding a compound containing an isocyanate functional group into an organic solvent to prepare a solution 2; (3) adding the prepared "solution 2" to "solution 1", stirring for reaction, and removing the solvent to obtain a coated vulcanizing agent; Wherein, the amphiphilic block copolymer in step (1) is polystyrene-polyoxyethyleneimine (PS-b-PEI) and / or polystyrene-polyacrylamide (PS-b-PAM); and the compound containing an isocyanate functional group in step (2) includes one or more of isophorone diisocyanate, toluene diisocyanate, diphenylmethane diisocyanate, hexamethylene diisocyanate, methylene di(4-cyclohexyl isocyanate), and tetramethylxylene diisocyanate.
2. A coated vulcanizing agent according to claim 1, characterized in that: In step (1), the mass ratio of CS2:S is 10:3-4, the volume ratio of CS2 solution to isopropanol is 1:1-3, and the volume ratio of isopropanol to toluene is 10:0.5-3; The surfactant is one or more of fatty acid glyceride, fatty acid sorbitan, polysorbate, sodium lauryl sulfate, and sodium lauryl sulfonate.
3. A coated vulcanizing agent according to claim 1, characterized in that: The organic solvent in step (2) is diphenyl ether and / or toluene.
4. A coated vulcanizing agent according to claim 1, characterized in that: The reaction temperature in step (3) is 10-60°C.
5. An asphalt stabilizer prepared by using the coated vulcanizing agent as described in any one of claims 1 to 4, characterized in that: The composition includes the following components in parts by weight:
6. The asphalt stabilizer according to claim 5, characterized in that The accelerator comprises one or more of thiurams, thiazoles, dithiocarbamates, and aldehyde amines; The auxiliary promoter comprises one or more of zinc oxide, magnesium oxide, magnesium carbonate, calcium oxide and calcium carbonate; The activated carbon has a mesh size of 100 to 400.
7. A method for preparing the asphalt stabilizer according to claim 5, characterized in that: The steps are as follows: The coated vulcanizing agent and activated carbon are mixed at 50°C for 20 to 30 minutes, and after adding the accelerator and the co-accelerator, the mixture is continued to be mixed for 30 to 40 minutes.
8. Use of the asphalt stabilizer prepared according to claim 7 in the preparation of anti-segregation modified asphalt materials.
9. The use according to claim 8, characterized in that: The asphalt stabilizer is added in an amount of 0.3%-0.4% of the total weight of the modified asphalt.
Citation Information
Patent Citations
Chiral resolution method for simulating magnetic ore dressing and special magnetic enrichment type nano inhibitor
CN110871141A
Process for the preparation of microcapsules
US5866153A